2021
DOI: 10.1200/jco.2021.39.15_suppl.2612
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human, phase I study of PF-06753512, a vaccine-based immunotherapy regimen (PrCa VBIR), in biochemical relapse (BCR) and metastatic castration-resistant prostate cancer (mCRPC).

Abstract: 2612 Background: Therapeutic vaccines targeting PC-associated antigens represent attractive approaches in combination with immune checkpoint inhibitors (ICI). Safety/antitumor activity of PF-06753512 (PrCa VBIR) was evaluated in a phase I, dose-escalation and expansion study in patients (pts) with BCR prior to ADT and in pts with mCRPC either prior to or after failure of novel hormone therapy. PrCa VBIR consists of: 1) priming immunization with a replication-deficient adenoviral vector (AdC68) expressing PSA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This approach was used in a large phase I trial including patients with different stages of prostate cancer, and three antigens were targeted (PSA, PSMA and prostate stem cell antigen). Although not yet published in a peer-reviewed journal, results from this trial showed few objective tumour responses and grade 3 or 4 adverse events in 38% of patients 154 . Consequently, this approach is not being further pursued.…”
Section: Antigen-specific Vaccinesmentioning
confidence: 83%
“…This approach was used in a large phase I trial including patients with different stages of prostate cancer, and three antigens were targeted (PSA, PSMA and prostate stem cell antigen). Although not yet published in a peer-reviewed journal, results from this trial showed few objective tumour responses and grade 3 or 4 adverse events in 38% of patients 154 . Consequently, this approach is not being further pursued.…”
Section: Antigen-specific Vaccinesmentioning
confidence: 83%
“…Once administered, the virus contributes to the production of inflammation in TME, while tumor peptides carried by the virus are presented to their specific T cells to potentiate an anti-tumor response. The idea of using adenoviruses for vaccination has been widely explored for cancer [8] and infectious diseases [9], but in most cases, it involves the genetic modification of the virus. After the adenovirus infection, the antigen will be expressed until the virus is completely cleared.…”
mentioning
confidence: 99%